Ennis Franciscan Friary, loose fragments, jamb - O'Donovan, Danielle (My University, 2008)
Loose fragment, jamb moulding comprising: broken quadrant, hollow chamfer, quadrant, right-angled rebate, quadrant, hollow chamfer, quadrant.
Keywords: Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Late Medieval; roll moldings; moldings, hollow; fillets (moldings)